Association Between Objectively Measured Physical Activity And Depression Symptoms - Dover, Sara (East Carolina University, 2015)
Purpose: Previous studies examining the relationship between depression and physical activity have been epidemiological in nature and have measured physical activity subjectively. The purpose of the present study is to examine the association between objectively measured physical activity and depressive symptoms. Methods: The study sample included 24 sedentary obese participants (3 male, 21 female) with elevated waist circumference and one additional cardiovascular risk factor. To assess depression, participants completed the Patient Health Questionnaire (PHQ-9). Average steps/day were measured over the course of 7-consecutive days using a Lifecorder Plus pedometer (Lees Summit, Missouri). Pearson correlations were performed to evaluate the association between average steps/day and depression. Results: The study sample had a mean (SD) body mass index of 34.7 (± 4.2 kg/m2), a mean steps/day of 5310.6 (± 2041.3 steps/day), and a mean PHQ-9 score of 3.0 (± 2.6). Average step counts were not significantly associated with PHQ (r=0.17, p=0.44). Conclusion: The results of the present study suggest that there is no association between objectively determined step counts and depression. The present analysis may be limited by a constrained range of physical activity levels and depression scores, and the small sample size.
Association between objectively measured physical activity and depression
Keywords: Kinesiology; Exercise; Depression, Mental